NANOCRISTAIS DE CELULOSE A PARTIR DE CELULOSE BACTERIANA - Lima,Lais R. (2015)
Bacterial cellulose produced from Gluconacetobacter xilinus was used to produce cellulose nanocrystals by sulfuric acid hydrolysis. Hydrolysis was performed with 64% sulfuric acid at 50 ºC with the hydrolysis time ranging between 5 and 90 min. The production of nanocrystals was observed to have size distributions that were dependent on hydrolysis times up to 10 min, after which time the suspensions showed distributions closer in size. Results from thermal analysis and X-ray diffraction showed that the amorphous cellulose was removed, leaving only the crystalline portion. Self-supported films were formed from the suspension of nanocrystals and had iridescence characteristics. The films were characterized by microscopy measures and specular reflectance.